A Low Expression of NRF2 Enhances Oxidative Stress and Autophagy in Myofibroblasts, Promoting Progression of Chronic Obstructive Pulmonary Disease - Guan, Pin; Cai, Wentao; Zhong, Chunrong; Jiang, Fan; Wu, Jinchan; Zhai, Xin (Current Medicinal Chemistry, 2025)
BackgroundThe inflammation phenotypes are often closely related to oxidative stress and autophagy pathway activation, which could be developed as a treatment target.AimsThe aim of this study was to explore the underlying mechanism of inflammation in chronic obstructive pulmonary disease (COPD). MethodsThe lung tissue single-cell RNA-seq (scRNA-seq) dataset of GSE171541 was downloaded from the Gene Expression Omnibus (GEO) database. The marker genes were obtained from the CellMarker database. “Seurat” and “harmony” R packages were used for single-cell profiling analysis. Then, the “AUCell” R package was employed to calculate the reactive oxygen species (ROS) and autophagy pathway scores. Gene regulation network analysis was performed by applying the “SCENIC” package, followed by conducting correlation analysis with Spearman’s rank correlation method. The cigarettes were used to develop a COPD model in mice, and the expression of relevant genes was measured by qRT-PCR.ResultsThe scRNA-seq analysis classified 12 cell subgroups in which the contractility of myofibroblasts was closely associated with the progression of COPD. Further analysis showed that ROS and autophagy pathways were significantly activated in myofibroblasts and that the nuclear factor erythroid 2-related factor 2 (NRF2) and its mediated oxidative stress pathway were inhibited in myofibroblasts. In addition, the downregulated NRF2 gene was negatively correlated with the expression of autophagy and ROS activation. In the COPD mice model, NRF2 was downregulated in COPD mice but further elevated in the COPD+NRF2 mice group. Interestingly, the mRNA levels of Kelch- like ECH-associated protein 1 (Keap1), NADPH oxidase (NOX), and Cathepsin B (CTSB) were upregulated in COPD group in comparison to the control group but they were downregulated by NRF2. These results suggested that low-expressed NFR2 promoted autophagy and ROS pathway activation in myofibroblasts for COPD progression.ConclusionWe identified a cell myofibroblast cluster closely associated with COPD progression using the scRNA-seq analysis. The downregulated NFR2, as a key risk factor, mediated myofibroblast death by activating the oxidative stress and autophagy pathway for COPD progression.
Keywords: autophagy